Properties of fiberglass crossarm in transmission tower - a review - Nadhirah A.; Beddu S.; Mohamad D.; Zainoodin M.; Nabihah S.; Mubin N.; Agusril; Itam Z.; Mansor H.; Kamal N.M.; Alam M.A.; Muda Z.C.; et al. (Research India Publications, 2023)
The main structure of the transmission line is the transmission tower. Transmission towers design must endure the weight of the trans-mission conductor at a certain height from ground. One of the main structures in transmission tower is crossarm. Crossarms of the trans-mission tower supports the transmission conductor. This paper is a review of past studies on fiberglass crossarm based on its mechanical properties and electrical performances. The aim of this paper is to analyze the mechanical properties which is including its tensile strength, elongation and hardness. It was discovered that the tensile strength increasing while hardness and elongation at break decreasing. In addition, the fiberglass has greater lightning power strength than the wood crossarm. It can be concluded that fiberglass crossarm can be used to replace conventional timber crossarm. Research India Publications.